Vaccination of chickens against Newcastle disease with a food pellet vaccine - Ideris, Aini; Ibrahim, A. Latif; Spradbrow, P.B. (Taylor and Francis Group, 1990)
The Australian, heat‐resistant, a virulent V4 strain of Newcastle disease (ND) virus was selected for further heat resistance to give a variant designated V4‐UPM. V4‐UPM was sprayed on to food pellets which were fed to chickens in amounts calculated to give about 106EID50 per chicken. Chickens vaccinated only once by feeding developed no haemagglutination‐inhibition (HI) antibodies and were not protected against challenge with a viscerotropic velogenic strain of ND virus.